1986
DOI: 10.1145/7921.11325
|View full text |Cite
|
Sign up to set email alerts
|

On the storage requirement in the out-of-core multifrontal method for sparse factorization

Abstract: Two techniques are introduced to reduce the working storage requirement for the recent multifrontal method of Duff and Reid used in the sparse out-of-core factorization of symmetric matrices. For a given core size, the reduction in working storage allows some large problems to be solved without having to use auxiliary storage for the working arrays. Even if the working arrays exceed the core size, it will reduce the amount of input-output traffic necessary to manipulate the working vectors. Experimental result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 6 publications
0
51
0
Order By: Relevance
“…The trees arising in this context are in-trees (as said before, there is no difference between in-trees and out-trees). Liu [34] discusses how to find the best traversal for the MINMEMORY problem when the traversal is required to correspond to a postorder traversal of the tree. In the follow-up study [35], an exact algorithm is proposed to solve the MINMEMORY problem, without the postorder constraint on the traversal.…”
Section: Case Study: Memory-aware Schedulingmentioning
confidence: 99%
See 2 more Smart Citations
“…The trees arising in this context are in-trees (as said before, there is no difference between in-trees and out-trees). Liu [34] discusses how to find the best traversal for the MINMEMORY problem when the traversal is required to correspond to a postorder traversal of the tree. In the follow-up study [35], an exact algorithm is proposed to solve the MINMEMORY problem, without the postorder constraint on the traversal.…”
Section: Case Study: Memory-aware Schedulingmentioning
confidence: 99%
“…Liu [34] has characterized the best postorder traversal, leading to a fast but sub-optimal solution for MINMEMORY. In a nutshell, the best postorder is obtained by guaranteeing that in the resulting order, the children of a node are listed in the increasing order of the memory requirement of their respective subtrees.…”
Section: Postorder Traversalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods used to achieve this goal are described in [65,85,86]. The survey by George and Liu [88] lists, inter alia, the following improvements and algorithmic follow-ups: mass eliminations [90], where it is shown that, in case of finite-element problems, after a minimum degree vertex is eliminated a subset of adjacent vertices can be eliminated next, together at the same time; indistinguishable nodes [87], where it is shown that two adjacent nodes having the same adjacency can be merged and treated as one; incomplete degree update [75], where it is shown that if the adjacency set of a vertex becomes a subset of the adjacency set of another one, then the degree of the first vertex does not need to be updated before the second one has been eliminated; element absorption [66], where based on a compact representation of elimination graphs, redundant structures (cliques being subsets of other cliques) are detected and removed; multiple elimination [134], where it was shown that once a vertex v is eliminated, if there is a vertex with the same degree that is not adjacent to the eliminated vertex, then that vertex can be eliminated before updating the degree of the vertices in adj (v), that is the degree updates can be postponed; external degree [134], where instead of the true degree of a vertex, the number of adjacent and indistinguishable nodes is used as a selection criteria. Some further improvements include the use of compressed graphs [11], where the indistinguishable nodes are detected even before the elimination process and the graph is reduced, and the extensions of the concept of the external degree [44,94].…”
Section: Labelling or Orderingmentioning
confidence: 99%
“…The frontal matrices that are allocated at any given time reside on one path from a root of the etree to some of its descendants. By delaying the allocation of the frontal matrix until after we factor the first child of j and by cleverly restructuring the etree, one can reduce the maximum size of the frontal-matrices stack [Liu 1986]. …”
Section: Left-looking-factor( a S)mentioning
confidence: 99%